2012
DOI: 10.1111/j.1365-2745.2011.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Realistic plant species losses reduce invasion resistance in a California serpentine grassland

Abstract: Summary1. The majority of experiments examining effects of species diversity on ecosystem functioning have randomly manipulated species richness. More recent studies demonstrate that realistic species losses have dramatically different effects on ecosystem functioning than those of randomized losses, but these results are based primarily on microcosm experiments or modelling efforts. 2. We conducted a field-based experiment directly comparing the consequences of realistic and randomized plant species losses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 51 publications
(91 reference statements)
7
56
1
Order By: Relevance
“…In prior work, we found that both biomass and nitrogen acquisition increase with seaweed richness (Bracken and Stachowicz 2006, Stachowicz et al 2008. Importantly, we also found that the biodiversity-ecosystem function relationship depended on natural, nonrandom patterns in seaweed biodiversity , highlighting the growing recognition that realistic nonrandom changes in biodiversity, such as the ones we consider here, can have profound influences on ecosystem function that are not predicted from studies of random assemblages (Ostfeld and LoGiudice 2003, Zavaleta and Hulvey 2004, Selmants et al 2012. Understanding the functional consequences of realistic changes in biodiversity needs to be based on elucidation of the factors underlying diversity patterns in the field.…”
Section: Introductionmentioning
confidence: 82%
“…In prior work, we found that both biomass and nitrogen acquisition increase with seaweed richness (Bracken and Stachowicz 2006, Stachowicz et al 2008. Importantly, we also found that the biodiversity-ecosystem function relationship depended on natural, nonrandom patterns in seaweed biodiversity , highlighting the growing recognition that realistic nonrandom changes in biodiversity, such as the ones we consider here, can have profound influences on ecosystem function that are not predicted from studies of random assemblages (Ostfeld and LoGiudice 2003, Zavaleta and Hulvey 2004, Selmants et al 2012. Understanding the functional consequences of realistic changes in biodiversity needs to be based on elucidation of the factors underlying diversity patterns in the field.…”
Section: Introductionmentioning
confidence: 82%
“…However, the vast majority of these studies have evaluated the effects of random diversity changes (Bracken et al 2008, Selmants et al 2012) on a single ecosystem function (Bracken and Stachowicz 2006, Hector and Bagchi 2007, Gamfeldt et al 2008). This lack of realism has resulted in valid criticisms with respect to the conservation implications of research into the effects of biodiversity on ecosystem functioning (Srivastava and Vellend 2005), which is particularly concerning because this body of work is motivated, at least in part, by the current global biodiversity crisis (Hooper et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of realism has resulted in valid criticisms with respect to the conservation implications of research into the effects of biodiversity on ecosystem functioning (Srivastava and Vellend 2005), which is particularly concerning because this body of work is motivated, at least in part, by the current global biodiversity crisis (Hooper et al 2005). Making biodiversity research more relevant to the natural world, where changes in biodiversity are nonrandom (Selmants et al 2012, Williams et al 2013, therefore requires evaluating the effects of nonrandom diversity changes (those that mimic biodiversity gains and losses quantified in the field) on a variety of different functions (Duffy 2009, Naeem et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on community-level responses to biodiversity loss reported evidence either consistent with (Buonopane, Huenneke & Remmenga 2005;Polley et al 2006;Phoenix et al 2008;Gilbert, Turkington & Srivastava 2009;Munson & Lauenroth 2009) or against (Symstad & Tilman 2001;Zavaleta & Hulvey 2004;Wardle, Lagerstr€ om & Nilsson 2008;Selmants et al 2012) predictions from mass ratio theory. However, identity effects associated with key attributes (other than biomass) of species being deleted could only be inferred (McLaren & Turkington 2010).…”
Section: F U N C T I O N a L G R O U P B I O M A S S A N D I D E N T mentioning
confidence: 76%